Aging-resistant and bending-resistant composite film and preparation method thereof

CN122896516APending Publication Date: 2026-10-13SHENZHEN JIKAIFENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611174160.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]然而,现有技术存在以下技术缺陷:耐老化与耐弯折性能难以兼得,提高交联度或添加刚性填料虽然能增强耐老化性能,但会降低材料的柔韧性和抗弯折疲劳性能;反之,增加柔性组分虽能改善弯折性能,却会加速热氧老化和光老化过程,影响使用寿命,为此本申请提出一种耐老化耐弯折复合膜及其制备方法来解决这一问题

Benefits of technology

本发明是一种耐老化耐弯折复合膜及其制备方法,采用第一表层、第一界面层、中间过渡层、第二界面层、第二表层的五层结构设计,各层之间呈连续过渡且无突变界面,同时第一表层高交联且凝胶含量85%-98%,提供优异的耐热氧老化性能,第二表层低交联且凝胶含量30%-65%,赋予材料良好的柔韧性和抗反复弯折性能,第一界面层和第二界面层的凝胶含量分别介于相邻两层之间且连续变化,避免了传统多层结构中因交联度突变而产生的界面应力集中问题,使两种看似矛盾的性能在同一材料体系中协同共存,具有耐老化和抗折弯的特点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122896516A_ABST
    Figure CN122896516A_ABST
Patent Text Reader

Abstract

The application discloses an anti-aging and anti-bending composite film and a preparation method thereof. The composite film comprises a first surface layer, a first interface layer, an intermediate transition layer, a second interface layer and a second surface layer in sequence along the thickness direction, and the layers are continuously transitioned and have no abrupt interface. The crosslinking density of the composite film is continuously gradient-distributed from the first surface layer to the second surface layer. The gel content of the first surface layer is 85%-98%, the gel content of the second surface layer is 30%-65%, the gel content of the first interface layer is 70%-85%, the gel content of the second interface layer is 35%-50%, and the gel content of the intermediate transition layer is 50%-70%. The preparation method comprises modified nano filler preparation, nano confinement enhancement layer preparation, multi-layer co-extrusion molding and single-side irradiation gradient crosslinking. Through the synergistic mechanism of gradient crosslinking, nano confinement and asymmetric stress dissipation, the composite film has excellent anti-aging performance and anti-bending performance, and can be widely applied to the fields of flexible display, wearable devices, flexible circuit boards and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite membrane technology, and more specifically, to an aging-resistant and bend-resistant composite membrane and its preparation method. Background Technology

[0002] With the rapid development of flexible electronics technology, the performance requirements for substrate and packaging materials in products such as flexible display devices, wearable smart devices, and flexible printed circuit boards are increasing. Among them, composite film materials, as a key component of flexible devices, must possess excellent resistance to bending fatigue to meet the requirements of repeated bending and rolling, and also have good resistance to aging to resist the erosion of environmental factors such as heat, oxygen, light, and humidity during long-term use.

[0003] In existing technologies, the following technical solutions are commonly used to improve the bending resistance of composite films: First, flexible elastomer components, such as thermoplastic polyurethane and polyolefin elastomers, are added to the polymer matrix to reduce the overall modulus and improve flexibility. Second, a multi-layer composite structure is used, alternating rigid and flexible layers to improve bending life through interlayer stress dissipation. To improve aging resistance, hindered amine light stabilizers, antioxidants, and other small-molecule additives are typically added, or highly weather-resistant resins such as polyimide and fluoropolymers are used as surface materials.

[0004] However, existing technologies have the following technical defects: it is difficult to achieve both aging resistance and bending resistance. Increasing the degree of crosslinking or adding rigid fillers can enhance aging resistance, but it will reduce the flexibility and bending fatigue resistance of the material. Conversely, increasing flexible components can improve bending performance, but it will accelerate the thermo-oxidative aging and photo-aging processes, affecting the service life. Therefore, this application proposes an aging-resistant and bending-resistant composite film and its preparation method to solve this problem.

[0005] No effective solutions have yet been proposed to address the problems in the relevant technologies. Summary of the Invention

[0006] The purpose of this invention is to provide an aging-resistant and bend-resistant composite film and its preparation method, so as to solve the problems mentioned in the background art.

[0007] To achieve the above objectives, the present invention provides the following technical solution: an aging-resistant and bend-resistant composite membrane and its preparation method, comprising, along the thickness direction, a first surface layer, a first interface layer, an intermediate transition layer, a second interface layer, and a second surface layer; the first surface layer and the first interface layer, the first interface layer and the intermediate transition layer, the intermediate transition layer and the second interface layer, and the second interface layer and the second surface layer all exhibit continuous transitions without abrupt interfaces; the crosslinking density of the composite membrane exhibits a continuous gradient distribution from the first surface layer to the second surface layer, wherein the gel content of the first surface layer is 85%-98%, the gel content of the second surface layer is 30%-65%, the gel content of the first interface layer is 70%-85%, the gel content of the second interface layer is 35%-50%, and the gel content of the intermediate transition layer is 50%-70%.

[0008] Further, the first surface layer is composed of polymethyl methacrylate (PMMA) and contains two-dimensional nanofillers. The surface of the two-dimensional nanofillers is in-situ grafted with polymer molecular brushes having the same chemical structure as the polymer matrix, forming a nano-confined interface layer. The two-dimensional nanofillers are graphene oxide, and the grafting density of the polymer molecular brushes is 0.05-0.5 chains / nm². The elastic modulus of the first surface layer is 3-8 GPa. The second surface layer is composed of thermoplastic polyurethane, and the elastic modulus of the second surface layer is 0.05-0.5 GPa. The intermediate transition layer is composed of a strain-hardening thermoplastic elastomer, and the gel content of the intermediate transition layer is 45%-75%. The difference in gel content between the first interface layer and the intermediate transition layer, and between the intermediate transition layer and the second interface layer, does not exceed 15% / μm. The first interface layer and the second interface layer are formed by mutual diffusion of two adjacent layers of materials during co-extrusion. The elastic modulus of the first interface layer decreases gradually from the first surface layer side to the intermediate transition layer side, and the elastic modulus of the second interface layer decreases gradually from the intermediate transition layer side to the second surface layer side.

[0009] A method for preparing an aging-resistant and bend-resistant composite film includes the following steps: (1) Disperse two-dimensional nanofillers in reactive monomers to allow in-situ polymerization on the surface of the two-dimensional nanofillers, forming modified nanofillers with polymer molecular brushes grafted on the surface. (2) The modified nanofiller obtained in step (1) is blended with the first surface matrix resin to form a nano-confined reinforcement layer material; (3) The nano-confined reinforcement layer material is used as the first surface layer material, and a five-layer composite structure is formed by multi-layer co-extrusion process with the intermediate transition layer material and the second surface layer material. The first surface layer and the intermediate transition layer, and the intermediate transition layer and the second surface layer are formed by interlayer diffusion in the co-extrusion die to form a continuously changing first interface layer and second interface layer. (4) The five-layer composite structure obtained in step (3) is subjected to unilateral irradiation treatment. The irradiation direction is incident from the first surface layer side, so that the irradiation dose decreases exponentially from the first surface layer to the second surface layer, forming a crosslinking density gradient distribution. The gel content of the first surface layer is 85%-98%, the gel content of the second surface layer is 30%-65%, the gel content of the intermediate transition layer is 50%-70%, and the gel content of the first interface layer and the second interface layer are respectively between the two adjacent layers and change continuously. After irradiation, the composite film is cooled to room temperature by cooling rollers, and then pulled and wound to obtain the finished composite film.

[0010] Further, the in-situ polymerization in step (1) is carried out by at least one of atom transfer radical polymerization, reversible addition-fragmentation chain transfer polymerization, or ring-opening polymerization; the multilayer co-extrusion in step (3) is carried out by co-extrusion blow molding or co-extrusion casting process, the co-extrusion die temperature is 190-240℃, and the width of the interface layer is controlled by adjusting the residence time of each layer of melt in the die, so that the thickness of the first interface layer and the second interface layer are each independently 5%-15% of the total thickness of the composite film; the single-sided irradiation treatment in step (4) is carried out by electron beam irradiation, the irradiation voltage is 80-200kV, and the irradiation dose is 30-150kGy; the temperature of the composite film is controlled at 10-30℃ below the glass transition temperature during irradiation, and the irradiated surface is protected by inert gas; the penetration depth is controlled by adjusting the irradiation voltage, so that the irradiation dose on the second surface layer side is reduced to 20%-50% of that on the first surface layer side.

[0011] Compared with the prior art, the present invention has the following beneficial effects: This invention relates to an aging-resistant and bend-resistant composite membrane and its preparation method. It employs a five-layer structure design consisting of a first surface layer, a first interface layer, an intermediate transition layer, a second interface layer, and a second surface layer. The layers are continuously transitioned without abrupt interfaces. The first surface layer is highly cross-linked with a gel content of 85%-98%, providing excellent resistance to heat and oxygen aging. The second surface layer is low in cross-linking with a gel content of 30%-65%, imparting good flexibility and resistance to repeated bending. The gel content of the first and second interface layers varies continuously between adjacent layers, avoiding the interfacial stress concentration problem caused by abrupt changes in cross-linking degree in traditional multilayer structures. This allows two seemingly contradictory properties to coexist synergistically within the same material system, resulting in both aging resistance and bend resistance. This invention relates to an aging-resistant and bend-resistant composite film and its preparation method. The first surface layer is composed of polymethyl methacrylate and contains graphene oxide with polymer molecular brushes grafted on its surface, forming a nano-confined interface layer. The movement of the confined polymer chain segments is hindered, and the activation energy of thermo-oxidative degradation is significantly increased, thereby delaying the aging process. At the same time, the chemically bonded interfacial bonding force ensures that the nanofiller does not debond during repeated bending, avoiding the technical defects of traditional physical blend fillers that are prone to agglomeration and debonding. Attached Figure Description

[0012] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0013] Figure 1 This is a schematic diagram of the structure of an aging-resistant and bend-resistant composite film according to an embodiment of the present invention; Figure 2 This is a schematic diagram of the internal structure of an aging-resistant and bend-resistant composite film according to an embodiment of the present invention; Figure 3 This is a schematic diagram of the production steps of an aging-resistant and bend-resistant composite film and its preparation method according to an embodiment of the present invention.

[0014] Figure label: 1. Composite membrane; 2. First surface layer; 3. Intermediate transition layer; 4. Second surface layer; 5. First interface layer; 6. Second interface layer. Detailed Implementation

[0015] The invention will now be further described with reference to the accompanying drawings and specific embodiments: Please see Figure 1-3According to an embodiment of the present invention, an aging-resistant and bend-resistant composite film comprises, along its thickness direction, a first surface layer, a first interface layer, an intermediate transition layer, a second interface layer, and a second surface layer. The first surface layer and the first interface layer, the first interface layer and the intermediate transition layer, the intermediate transition layer and the second interface layer, and the second interface layer and the second surface layer all exhibit continuous transitions without abrupt interface changes. The crosslinking density of the composite film exhibits a continuous gradient distribution from the first surface layer to the second surface layer, wherein the gel content of the first surface layer is 85%-98%, the gel content of the second surface layer is 30%-65%, the gel content of the first interface layer is 70%-85%, the gel content of the second interface layer is 35%-50%, and the gel content of the intermediate transition layer is 50%-70%. Through the synergistic mechanism of gradient crosslinking, nano-confinement, and asymmetric stress dissipation, the present invention enables the composite film to possess both excellent aging resistance and bend resistance, and can be widely applied in flexible displays, wearable devices, flexible circuit boards, and other fields.

[0016] According to the above-described scheme of the present invention, the first surface layer is composed of polymethyl methacrylate and contains two-dimensional nanofillers. Polymer molecular brushes with the same chemical structure as the polymer matrix are grafted in situ onto the surface of the two-dimensional nanofillers to form a nano-confined interface layer. The two-dimensional nanofillers are graphene oxide, and the grafting density of the polymer molecular brushes is 0.05-0.5 chains / nm². The elastic modulus of the first surface layer is 3-8 GPa. The second surface layer is composed of thermoplastic polyurethane and has an elastic modulus of 0.05-0.5 GPa. The intermediate transition layer is composed of strain-hardening thermoplastic elastomer and has a gel content of 45%-75%. The difference in gel content between the first interface layer and the intermediate transition layer, and between the intermediate transition layer and the second interface layer, does not exceed 15% / μm. The first and second interface layers are formed by mutual diffusion of adjacent materials during co-extrusion. The elastic modulus of the first interface layer decreases gradually from the first surface layer side to the intermediate transition layer side, and the elastic modulus of the second interface layer decreases gradually from the intermediate transition layer side to the second surface layer side.

[0017] A method for preparing an aging-resistant and bend-resistant composite film includes the following steps: (1) Preparation of modified nanofillers Five kilograms of graphene oxide nanosheets with a particle size of 50-200 nm were dispersed in 100 L of anhydrous toluene and ultrasonically dispersed for 30 minutes at an ultrasonic power of 800 W and a frequency of 30 kHz. The dispersed suspension was transferred to a jacketed reactor, and 1 L of 3-aminopropyltriethoxysilane coupling agent was added. Nitrogen gas was introduced for protection, and the mixture was heated to 80 °C and reacted for 6 hours. After the reaction, the solid was separated by centrifugation and washed three times with anhydrous ethanol.

[0018] The surface-aminated graphene oxide was redispersed in 50 L of dimethylformamide, transferred to a reaction vessel, and 1.5 L of 2-bromoisobutyryl bromide and 1 L of triethylamine were added. The system temperature was controlled at 0-5 °C by turning on the low-temperature circulating bath, and the reaction was carried out for 4 hours. After the reaction was completed, the mixture was centrifuged, washed three times with dichloromethane, and dried under vacuum.

[0019] The above-mentioned graphene oxide with an initiator fixed on its surface was dispersed in a mixed solvent of 20 L of methyl methacrylate monomer and 30 L of toluene. 0.2 kg of cuprous bromide and 0.3 L of pentamethyldiethylenetriamine were added, and the mixture was purged with nitrogen and heated to 60-80 °C for 8-12 hours. After the reaction, the mixture was centrifuged, washed three times with tetrahydrofuran, and vacuum dried to obtain modified graphene oxide with polymethyl methacrylate molecular brushes grafted onto its surface. GPC analysis showed that the number-average molecular weight of the grafted molecular brushes was 8500 g / mol, and the molecular weight distribution coefficient was 1.21; thermogravimetric analysis showed that the grafting density was 0.18 chains / nm².

[0020] (2) Preparation of nano-confined reinforcement layer 3 kg of the modified graphene oxide and 100 kg of polymethyl methacrylate resin were added to a high-speed mixer at 1000 rpm for 10 minutes. The premixed material was then fed into a twin-screw extruder via a loss-in-weight metering feeder. The extruder temperature settings were: feeding section 180℃, melting section 200℃, mixing section 210℃, homogenization section 210℃, die temperature 200℃, screw speed 300 rpm, and vacuum degree 0.06-0.08 MPa. The molten material was extruded into strips through the die, cooled in a water cooling tank at 20-30℃, and then granulated by a pelletizer to obtain nano-confined reinforcing layer granules.

[0021] (3) Multi-layer co-extrusion molding Nano-confined reinforcing layer granules and polymethyl methacrylate resin were mixed in a 1:1 ratio as the first surface layer material, polyester thermoplastic elastomer (strain hardening type, 20% strain modulus 8MPa, 100% strain modulus 32MPa) was used as the intermediate transition layer material, and thermoplastic polyurethane (elastic modulus 0.1GPa) was used as the second surface layer material. These materials were then added to three single-screw extruders.

[0022] Extruder temperature settings: First surface layer extruder 180-210℃, intermediate transition layer extruder 170-200℃, second surface layer extruder 160-190℃. The three layers of melt enter the five-layer co-extrusion die at a temperature of 200-220℃, forming a continuously varying first and second interface layer in the interlayer diffusion zone inside the die. Adjust the residence time of each melt layer so that the thickness of the first and second interface layers is 10% of the total thickness of the composite film.

[0023] After the melt is extruded from the die, it enters a three-roll calender for cooling and shaping. The temperatures of the three rolls are: 60℃ for the upper roll, 50℃ for the middle roll, and 40℃ for the lower roll. The total thickness is controlled at 100μm, and the layer thickness ratio is 25:50:25 for the first surface layer: intermediate transition layer: second surface layer.

[0024] (4) Unilateral irradiation treatment The five-layer composite membrane semi-finished product is installed on the unwinding machine, and the membrane surface tension is controlled at 80 N / m by the tension control system. Before the membrane material enters the irradiation chamber, the membrane surface temperature is controlled at 75-85℃ by the cooling roller group (PMMA has a Tg of 105℃, and 30℃ below Tg). High-purity nitrogen gas is introduced into the irradiation chamber, with an oxygen content of <100 ppm.

[0025] The composite film was irradiated unilaterally using an electron beam accelerator, with the irradiation direction being from the first surface layer side. The irradiation voltage was 120 kV, and the irradiation dose was 80 kGy. After irradiation, the gel content of the first surface layer was 92%, the gel content of the first interface layer was 78%, the gel content of the intermediate transition layer was 62%, the gel content of the second interface layer was 45%, and the gel content of the second surface layer was 48%. After irradiation, the composite film was cooled to room temperature by cooling rollers and then drawn and wound to obtain the finished composite film.

[0026] In the description of this invention, it should be noted that the terms "top," "bottom," "one side," "the other side," "front," "rear," "middle part," "inner," "top," and "bottom," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing the invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention. The terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance. Furthermore, unless otherwise explicitly specified and limited, the terms "installed," "connected," and "linked" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal communication of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.

[0027] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An aging-resistant and bend-resistant composite film, characterized in that, The composite film comprises, in sequence along its thickness direction: a first surface layer, a first interface layer, an intermediate transition layer, a second interface layer, and a second surface layer; the first surface layer and the first interface layer, the first interface layer and the intermediate transition layer, the intermediate transition layer and the second interface layer, and the second interface layer and the second surface layer all exhibit continuous transitions without abrupt interfaces; the crosslinking density of the composite film exhibits a continuous gradient distribution from the first surface layer to the second surface layer, wherein the gel content of the first surface layer is 85%-98%, the gel content of the second surface layer is 30%-65%, the gel content of the first interface layer is 70%-85%, the gel content of the second interface layer is 35%-50%, and the gel content of the intermediate transition layer is 50%-70%.

2. The aging-resistant and bending-resistant composite film according to claim 1, characterized in that, The first surface layer is made of polymethyl methacrylate and contains two-dimensional nanofillers. The surface of the two-dimensional nanofillers is grafted with polymer molecular brushes with the same chemical structure as the polymer matrix to form a nano-confined interface layer. The two-dimensional nanofillers are made of graphene oxide. The grafting density of the polymer molecular brushes is 0.05-0.5 chains / nm². The elastic modulus of the first surface layer is 3-8 GPa.

3. The aging-resistant and bending-resistant composite film according to claim 1, characterized in that, The second surface layer is made of thermoplastic polyurethane, and the elastic modulus of the second surface layer is 0.05-0.5 GPa.

4. The aging-resistant and bending-resistant composite film according to claim 1, characterized in that, The intermediate transition layer is composed of a strain-hardening thermoplastic elastomer, and the gel content of the intermediate transition layer is 45%-75%.

5. The aging-resistant and bending-resistant composite film according to claim 1, characterized in that, The difference in gel content between the first interface layer and the intermediate transition layer, and between the intermediate transition layer and the second interface layer, does not exceed 15% / μm. The first interface layer and the second interface layer are formed by mutual diffusion of two adjacent material layers during co-extrusion. The elastic modulus of the first interface layer decreases gradually from the first surface layer side to the intermediate transition layer side, and the elastic modulus of the second interface layer decreases gradually from the intermediate transition layer side to the second surface layer side.

6. A method for preparing an aging-resistant and bend-resistant composite film according to any one of claims 2-6, characterized in that, Includes the following steps: (1) Disperse the two-dimensional nanofiller in the reactive monomer and polymerize the two-dimensional nanofiller in situ on the surface to form a modified nanofiller with polymer molecular brush grafted on the surface. (2) The modified nanofiller obtained in step (1) is blended with the first surface matrix resin to form a nano-confined reinforcement layer material; (3) The nano-confined reinforcement layer material is used as the first surface layer material, and a five-layer composite structure is formed by multi-layer co-extrusion process with the intermediate transition layer material and the second surface layer material. The first surface layer and the intermediate transition layer, and the intermediate transition layer and the second surface layer are formed by interlayer diffusion in the co-extrusion die to form a continuously changing first interface layer and second interface layer. (4) The five-layer composite structure obtained in step (3) is subjected to unilateral irradiation treatment. The irradiation direction is incident from the first surface layer side, so that the irradiation dose decreases exponentially from the first surface layer to the second surface layer, forming a crosslinking density gradient distribution. The gel content of the first surface layer is 85%-98%, the gel content of the second surface layer is 30%-65%, the gel content of the intermediate transition layer is 50%-70%, and the gel content of the first interface layer and the second interface layer are respectively between the two adjacent layers and change continuously. After irradiation, the composite film is cooled to room temperature by cooling rollers, and then pulled and wound to obtain the finished composite film.

7. The method for preparing an aging-resistant and bend-resistant composite film according to claim 6, characterized in that, The in-situ polymerization in step (1) is carried out by at least one of atom transfer radical polymerization, reversible addition-fragmentation chain transfer polymerization or ring-opening polymerization; the multilayer co-extrusion in step (3) is carried out by co-extrusion blow molding or co-extrusion casting process, the co-extrusion die temperature is 190-240℃, and the width of the interface layer is controlled by adjusting the residence time of each layer of melt in the die, so that the thickness of the first interface layer and the second interface layer are each independently 5%-15% of the total thickness of the composite film.

8. The method for preparing an aging-resistant and bend-resistant composite film according to claim 6, characterized in that, The single-sided irradiation treatment in step (4) uses electron beam irradiation with an irradiation voltage of 80-200kV and an irradiation dose of 30-150kGy. During the irradiation process, the temperature of the composite film is controlled to be 10-30℃ below the glass transition temperature, and the irradiated surface is protected with inert gas. The penetration depth is controlled by adjusting the irradiation voltage so that the irradiation dose is attenuated to 20%-50% of that on the first surface side on the second surface side.